2012
DOI: 10.1371/journal.pone.0045621
|View full text |Cite
|
Sign up to set email alerts
|

Adipose Stromal Cells Amplify Angiogenic Signaling via the VEGF/mTOR/Akt Pathway in a Murine Hindlimb Ischemia Model: A 3D Multimodality Imaging Study

Abstract: Although adipose-derived stromal cell (ADSC) transplantation has been demonstrated as a promising therapeutic strategy for peripheral arterial disease (PAD), the mechanism of action behind the observed therapeutic efficacy of ADSCs remains unclear. This study was designed to investigate the long-term outcome and therapeutic behavior of engrafted ADSCs in a murine hindlimb ischemia model using multimodality molecular imaging approaches. ADSCs (1.0×107) were isolated from Tg(Fluc-egfp) mice which constitutively … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 48 publications
(45 citation statements)
references
References 37 publications
0
45
0
Order By: Relevance
“…1C). mADSCs GFP+ possessed multipotency and other characteristics of mADSCs as previously described (Fan et al, 2012). Laser Doppler perfusion imaging (LDPI) spatiotemporally visualized the change in peripheral blood perfusion (Fig.…”
Section: Restoration Of Hindlimb Ischemia In Aged CLI Model Followingmentioning
confidence: 99%
See 2 more Smart Citations
“…1C). mADSCs GFP+ possessed multipotency and other characteristics of mADSCs as previously described (Fan et al, 2012). Laser Doppler perfusion imaging (LDPI) spatiotemporally visualized the change in peripheral blood perfusion (Fig.…”
Section: Restoration Of Hindlimb Ischemia In Aged CLI Model Followingmentioning
confidence: 99%
“…Reporter gene imaging was performed to monitor Vegfr2-luc transcription level and mADSCs survival in vivo (Cao et al, 2006;Fan et al, 2012). For in vitro BLI, mADSCs…”
Section: Reporter Gene Imaging and Assaysmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, these cells show low survival rates when implanted, which once again supports that the regenerative effects could be due to their paracrine abilities. [26] There are also several studies which investigated the effects of ASCs administration on renovascular diseases. Administration of ASCs in pigs with renal artery stenosis restored renal hemodynamics and function.…”
Section: The Effects Of Ascs On Angiogenesismentioning
confidence: 99%
“…Under hypoxic stress in ischemic myocardium, the vascular endothelial growth factor (VEGF), basic fibroblast growth factor, hepatocyte growth factor, hypoxia inducible factor-1, and stromal cell-derived factor-1 are significantly increased in injured hearts treated with MSCs or multipotent stromal cells (30). With multimodality BLI/BLT/microCT imaging, we recently demonstrated multipotent adipose stromal cells therapy promoted recovery from hindlimb ischemia through enhancing proangiogenic signal in vivo, though the cells failed to incorporate into the host microvasculature as functional components (24). Using in vivo BLI, a recent study reported that porcine PSC-derived endothelial cells could also improve cardiac function after MI via release of proangiogenic and antiapoptotic factors in the ischemic microenvironment (31) (Fig.…”
Section: Molecular Imaging the Efficacy Of Donor Stem Cellsmentioning
confidence: 99%